Social Networks as a Supplement to the Public Media Service? – An Example of the Vukovar Protest in October 2018 - Blago Markota; Nika uho; Maja Odorjan (7th International OFEL Conference on Governance, Management and Entrepreneurship: Embracing Diversity in Organisations. April 5th - 6th, 2019, Dubrovnik, Croatia, 2019)
Generally, the mass media perform the following social functions: information function, agenda setting, control function and criticism of social structures and institutions, educational function and function of socialization and integration (Jurcic, 2017). Through the digital revolution the number of commercial media has increased considerably. Correspondingly, question arise: in which way, primarily commercial media, are fulfilling these social media functions today? Public media services, with legally prescribed obligation to perform these functions, are losing their audience. Excluding the trends of media privatization, commercialization and commodification through the development of digital technologies active citizen participation in public informing has expanded (Flew et al., 2009). The content produced by "ordinary" citizens placed on social networks prevails in the digital public sphere. The existing public media platforms are expressing the need for shifting their services into the digital public sphere in future business plans and to actively involve citizens (Strömblad et al., 2016). Our research question is to what extent and in which way Croatian citizens are fulfilling some of the social functions of mass media using social networks? To give the answer to the research question, the content analysis will be conducted within all posts published on Facebook in the period 10/10 until 10/17/18, which informed the public about the protest held in Vukovar. The Vukovar protest was one of the central social events and it was subject of numerous public and political debates. Nevertheless, the protest itself was not covered by national media broadcasters. This lack of coverage by central media platforms gives us the opportunity to analyse the role of social networks and their possibility to replace the functions of traditional media. We will examine whether the social networks content can adequately replace public media platforms or the content published in the case of Vukovar protest was dysfunctional, primarily regarding information and integration functions.
Keywords: 650; protest in Vukovar; public content; public media service; social networks